Faktor Determinan Pemanfaatan Posbindu - Isnani Nurhayati; Tri Yuniarti; Sri Sayekti Heni Sunaryanti; Sri Iswahyuni; Anas Rahmad Hidayat (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: Posbindu is part of the health service system covering promotive and preventive. Educational institution is dihambau to provide health facilities one of them Posbindu. Students are the most important part of educational institutions to support the need for healthy physical and psychological conditions. Posbindu can detect early risk of untransmitted diseases, including hypertension and obesity at the age of 18 years and above. Purpose of this study is to know the factors that affect the utilization of Posbindu. Methods: of research, a detailed analytical approach, the population of all active students in STIKES Mamba'ul ' Ulum Surakarta 258 people, sampling with purposive random sampling, a sample based on Solvin formula obtained from 94 respondents. Data retrieval using physical test result when in (BMI and blood pressure index) and questionnaire contains about the condition of the respondent's health and the utilization of in, each variable of ordinal and Inteval scale. Results: Respondents with a level of knowledge about Posbindu category quite 79%, BMI category ideal body weight 74%. Conslusion: Normal average blood pressure 65%, regular visit at Posbindu 2x visit. The results of a simple linear regression analysis test in the right factor on the utilization of Posbidu is knowledge, BMI and health status with a significance of 0.000 < 0.05.